2016
DOI: 10.1016/j.atherosclerosis.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variant in CAV1 increases susceptibility to coronary artery disease and myocardial infarction

Abstract: Background The CAV1 gene encodes caveolin-1 expressed in cell types relevant to atherosclerosis. Cav-1-null mice showed a protective effect on atherosclerosis under the ApoE−/− background. However, it is unknown whether CAV1 is linked to CAD and MI in humans. In this study we analyzed a tagSNP for CAV1 in intron 2, rs3807989, for potential association with CAD. Methods and Results We performed case-control association studies in three independent Chinese Han populations from GeneID, including 1,249 CAD cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 56 publications
3
45
0
3
Order By: Relevance
“…CAV1 SNP variants have been suggested to be linked to metabolic syndrome (MetS), a major risk factor for diabetes and coronary artery disease. Several CAV1 single-nucleotide polymorphisms (SNP) were found to associate with MetS: rs926198 in Caucasians and Hispanics [77], rs3807989 in the Chinese Han population [78], and rs1997623 in Kuwaiti children as shown by our previous study [79]. The forest plot in Figure 3 shows an association between LHDLC and MetS with the heterozygous genotype CA and the A-allele, meaning that a carrier of the A genotype has a higher chance of developing MetS in the studied population.…”
mentioning
confidence: 69%
“…CAV1 SNP variants have been suggested to be linked to metabolic syndrome (MetS), a major risk factor for diabetes and coronary artery disease. Several CAV1 single-nucleotide polymorphisms (SNP) were found to associate with MetS: rs926198 in Caucasians and Hispanics [77], rs3807989 in the Chinese Han population [78], and rs1997623 in Kuwaiti children as shown by our previous study [79]. The forest plot in Figure 3 shows an association between LHDLC and MetS with the heterozygous genotype CA and the A-allele, meaning that a carrier of the A genotype has a higher chance of developing MetS in the studied population.…”
mentioning
confidence: 69%
“…The frequencies of observed alleles and genotypes for these polymorphisms were in Hardy-Weinberg proportions in the controls. On the basis of inferred phenotypic manifestations [10, 2426], subjects who carried rare alleles of the eNOS 894T (coded for Aspartate), Cav-1 14713A , and 29107A were grouped together and considered a risk genotype in the following statistical analysis. For subjects who carried the homozygous eNOS GG genotype as a reference, a LAA stroke risk elevation was significant in carriers of combined GT/TT variant genotypes (OR = 1.72, 95% CI = 1.09–2.75).…”
Section: Resultsmentioning
confidence: 99%
“…Knockdown experiments of Cav-1 have been shown to cause cardiohypertrophy, diabetes, and pulmonary and focal cerebral ischemia and reperfusion injury [3941]. Recent genome wide association reports have shown that Cav-1 SNPs are associated with stroke disease and that the Cav-1 G14713A elevates risk of coronary artery disease and myocardial infarction [24, 4244]. However, some results are conflicting regarding the association between the Cav-1 polymorphisms and the risk of atrial fibrillation in cardiac arrhythmias [45].…”
Section: Discussionmentioning
confidence: 99%
“…Cav-1 proteininin plazma lipoprotein metabolizmasının düzenlenmesindeki rolü çok sayıda çalışmada gösteril-miştir (41,42). Ancak literatürde CAV1 gen varyasyonlarının kardiyovasküler hastalıklarla ilişkisini inceleyen sınırlı sayıda çalışma mevcuttur (27,29,30). Çalışmamızda incelediğimiz CAV1 rs3807989 polimorfizmi daha önceki çalışmalarda artmış atrial fibrilasyon riski ile ilişkili bulunmuştur (30).…”
Section: Yöntemunclassified
“…CAV1 gen varyasyonlarıyla ilgili yapılmış sınırlı sayıda çalışma mevcuttur (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Literatürde CAV1 gen varyasyonlarının diyabetle ilişkilendirilmiş kardiyovasküler hastalıklarla ilişkisini inceleyen bir araştırma bulunmamaktadır.…”
Section: Introductionunclassified